The Vienna Genesis: Material analysis and conservation of a Late Antique illuminated manuscript on purple parchment - Hofmann, Christa (2020)
Parchment, inks, dyes and pigments of the Vienna Genesis were investigated. The results formed the basis for conservation and storage of the illuminated manuscript